Platelet endothelial aggregation receptor-1 regulates bovine muscle satellite cell migration and differentiation via integrin beta-1 and focal adhesion kinase - Pang, Yusheng (Cell Adh Migr, 2019)
PEAR1 is highly expressed at bovine MDSC differentiation. However, its biological function remains unclear. Western blotting results showed that PEAR1 increased between day 0 and day 2 of cell differentiation and decreased from day 3. Moreover, scratch test showed that wound healing rate increased after PEAR1 overexpression and decreased upon its suppression. Meanwhile, we found that, upon PEAR1 induction, both the expression of the focal adhesion-associated and MyoG, and the myotube fusion rate increased. However, when PEAR1 was suppressed, opposite results were obtained. Immunoprecipitation revealed an association between PEAR1 and ITGB1. Notably, inhibition of FAK and ITGB1 repressed cell differentiation. In conclusion, our study indicated that PEAR1 is involved in the regulation of bovine MDSC migration and differentiation.